Rereading the English Common Reader: a Preface to a History of Audiences - Rose, Jonathan (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English] As a genre, the working-class autobiography originates around 1800 – here too the reading revolution marked a watershad, when common readers began to write about themselves. And they are often wonderfully forthcoming about their reading experiences – not only what they read, but how they comprehended and reacted to their reading. These sources open up a new scholarly frontier. They will make possible a third generation of reading history – a history of audiences, which would reverse the usual perspective of intellectual historiography. It would first define a mass audience, then determine its cultural diet, and ultimately measure the collective response of that audience not only to particular works of literature, but also to education, religion, art, and any other cultural activity. Whereas reception histories have generally traced the responses of professional intellectuals (literary and social critics, academics, clergymen), audience histories would focus on the common reader – defined as any reader who did not read books for a living. The British working-class reader happens to be my subject, but this essay offers general encouragement and advice for the study of common readers in all classes and all nations. It illustrates some of the questions a history of audiences could tackle, and points out the methodological problems it may involve.